Social media marketing and post purchase behavior: A concept Paper - Nivethika, A.; Kumaradeepan, V. (South Eastern University of Sri Lanka, 2024)
The aim of the research is to explore the impact of social media marketing on post-purchase behavior.The current modern era, social media marketing is very popular in all over the world. Number of research articles derived from internet sources on social media and consumer purchase behavior. Critical literature review has done to explore the connection between social media and consumer post purchase behavior. Interaction or Engagement Opportunities, Consistency, Differentiation, or Customization, Quality content Word of mouth are factors ofsocial media marketing. Committed customers, Repeat purchase, Increase use, brand switching and discontinued use were the dimensions of consumer post purchase behavior. Also found Trust has mediating variable between social media and consumer purchase behavior.
Keywords: Social media marketing; Social Media; Post purchase behavior; Conceptual Paper